An analytical full-scale model to predict thermal response in boreholes with groundwater advection. (5th March 2020) - Cai, Shanshan; Li, Xiaoyu; Zhang, Minghui; Fallon, James; Li, Kun; Cui, Tengfei
Highlights: Propose an improved analytical solution to predict thermal response in the borehole. Consider both effects of time scale and groundwater flow. Evaluate differences predicted by the proposed and other traditional models. Compare thermal responses in single and multiple boreholes with groundwater flow. Abstract: Borehole heat exchanger (BHE) is an important component in the ground coupled heat pump (GCHP) system. Based on the theories of composite medium line-source and the moving line-source, an analytical full time-scale model has been derived to predict the performance of BHE by considering the coupled effects of transient heat transfer in the borehole, the horizontal groundwater around the borehole and the axial heat conduction along the borehole. The full-scale model is validated by the experimental data and the numerical results. The validated model is applied to predict fluid temperature in the cases (i) with unit load, (ii) with annual building loads and (iii) with multiple boreholes. Based on the simulation results, the impacts of time length, axial conduction, groundwater flow and locations of boreholes are discussed in detail.